Elucidating the temporal and spatial dynamics of Biomphalaria glabrata genetic diversity in three Brazilian villages. Issue 10 (3rd August 2013) - Thiele, Elizabeth A.; Corrêa‐Oliveira, Guilherme; Gazzinelli, Andrea; Minchella, Dennis J.
Abstract: Objective: The freshwater snail Biomphalaria glabrata is the principal intermediate host for the parasite Schistosoma mansoni within Brazil. We assessed the potential effects of snail population dynamics on parasite transmission dynamics via population genetics. Methods: We sampled snail populations located within the confines of three schistosome‐endemic villages in the state of Minas Gerais, Brazil. Snails were collected from individual microhabitats following seasonal periods of flood and drought over the span of 1 year. Snail spatio‐temporal genetic diversity and population differentiation of 598 snails from 12 sites were assessed at seven microsatellite loci. Results: Average genetic diversity was relatively low, ranging from 4.29 to 9.43 alleles per locus, and overall, subpopulations tended to exhibit heterozygote deficits. Genetic diversity was highly spatially partitioned among subpopulations, while virtually, no partitioning was observed across temporal sampling. Comparison with previously published parasite genetic diversity data indicated that S. mansoni populations are significantly more variable and less subdivided than those of the B. glabrata intermediate hosts. Discussion: Within individual Brazilian villages, observed distributions of snail genetic diversity indicate temporal stability and very restricted gene flow. This is contrary to observations of schistosome genetic diversity over the same spatial scale, corroborating the expectation that parasite gene flow at the level of individual villages is likely driven by vertebrate host movement.